Digital Technology To Improve Marketing Strategy In The Era Of Pandemic Covid-19 - I Made Aditya Dharma; I Wayan Lasmawan; I Nengah Suastika (The Es Economics and Entrepreneurship, 2022)
In the current era of globalization, technology and information are growing rapidly, especially for digital marketing, it is needed by industries engaged in the sale of goods and services. Especially now that the Covid-19 Pandemic is impacting almost all sectors of life. The impact of the corona virus pandemic (Covid-19) is being felt in the business and economic world. Digital marketing is a very fast growing and inexpensive solution to reach maximum customers without any limits. Through digital marketing adjustments can convey messages only to potential customers and many new customers can be attracted by using different techniques. This study uses a qualitative descriptive research method with a case study approach. The results of the study concluded that social media has increased the performance of businesses and 90 percent of respondents consider social media important for their business. The main benefit derived from social media is brand awareness. From this research, other benefits obtained by respondents from social media for SMEs are: Increasing Traffic 72 percent, Increasing Ranking Searches 62 percent, New Partnerships 59 percent, Increasing Sales 48 percent, Reducing Marketing Costs 59 percent for self-employed, 58 percent for SMEs two times more likely to find qualified prospects.